1999
DOI: 10.1074/jbc.274.33.23443
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of ADAMTS11 , an Aggrecanase from the ADAMTS Family

Abstract: Aggrecan is responsible for the mechanical properties of cartilage. One of the earliest changes observed in arthritis is the depletion of cartilage aggrecan due to increased proteolytic cleavage within the interglobular domain. Two major sites of cleavage have been identified in this region at Asn 341 -Phe 342 and Glu 373 -Ala 374 . While several matrix metalloproteinases have been shown to cleave at Asn 341 -Phe 342 , an as yet unidentified protein termed "aggrecanase" is responsible for cleavage at Glu 373 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
325
1
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 470 publications
(335 citation statements)
references
References 57 publications
8
325
1
1
Order By: Relevance
“…The aggrecanases ADAM-TS4 and ADAM-TS5 are considered to be the principal proteinases responsible for cartilage proteoglycan degradation, and these enzymes contain the typical furin recognition motif (9,10). This study shows that the addition of a furin inhibitor to resorbing cartilage can partially block the breakdown of the proteoglycan matrix.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The aggrecanases ADAM-TS4 and ADAM-TS5 are considered to be the principal proteinases responsible for cartilage proteoglycan degradation, and these enzymes contain the typical furin recognition motif (9,10). This study shows that the addition of a furin inhibitor to resorbing cartilage can partially block the breakdown of the proteoglycan matrix.…”
Section: Discussionmentioning
confidence: 80%
“…Aggrecan fragments cleaved at this bond have been identified in cultures undergoing cartilage matrix degradation (5,6) and in arthritic synovial fluids (7,8). Two cartilage-derived aggrecanases have so far been identified that belong to a disintegrin and metalloproteinase with thrombospondin motifs (ADAM-TS) subfamily of proteinases; these are ADAM-TS4 (aggrecanase 1) (9) and ADAM-TS5 (aggrecanase 2) (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was initially described as a constitutively expressed aggrecanase in bovine (16,17) and human (18) chondrocytes, although we and others have demonstrated regulation by inflammatory cytokines in murine (4), bovine (19), and human (9) tissue. The putative promoter region of the gene has predicted binding sites for a number of transcription factors, including NF-B, which are likely to be involved in gene expression following activation of inflammatory signaling (20).…”
Section: Discussionmentioning
confidence: 98%
“…The same study also showed upregulation of the aggrecanases ADAMTS-4 (aggrecanase-1) and ADAMTS-5 (aggrecanase-2) by IL-1. These proteins belong to the disintegrin and metalloprotease with thrombospondin motifs family (61), and are the only enzymes that have been shown to cleave aggrecan at a site that generates the Glu373-Ala374 fragments (62,63) seen in interleukin-1 stimulated bovine explant cultures (64) and human synovial fluid of OA patients (65).…”
Section: Models Of Osteoarthritis In Articular Cartilagementioning
confidence: 99%